Differential Roles of Iron Storage Proteins in Maintaining the Iron Homeostasis in Mycobacterium tuberculosis - Khare, Garima (PLoS One, 2017)
Ferritins and bacterioferritins are iron storage proteins that represent key players in iron homeostasis. Several organisms possess both forms of ferritins, however, their relative physiological roles are less understood. Mycobacterium tuberculosis possesses both ferritin (BfrB) and bacterioferritin (BfrA), playing an essential role in its pathogenesis as reported by us earlier. This study provides insights into the role of these two proteins in iron homeostasis by employing M. tuberculosis bfr mutants. Our data suggests that BfrA is required for efficient utilization of stored iron under low iron conditions while BfrB plays a crucial role as the major defense protein under excessive iron conditions. We show that these two proteins provide protection against oxidative stress and hypoxia. Iron incorporation study showed that BfrB has higher capacity for storing iron than BfrA, which augurs well for efficient iron quenching under iron excess conditions. Moreover, iron release assay demonstrated that BfrA has 3 times superior ability to release stored iron emphasizing its requirement for efficient iron release under low iron conditions, facilitated by the presence of heme. Thus, for the first time, our observations suggest that the importance of BfrA or BfrB separately might vary depending upon the iron situation faced by the cell.